Structural coercion in the context of community engagement in global health research conducted in a low resource setting in Africa - Nyirenda, D; Sariola, S; Kingori, P; Squire, B; Bandawe, C; Parker, M; Desmond, N (BioMed Central, 2020)
BACKGROUND: While community engagement is increasingly promoted in global health research to improve ethical research practice, it can sometimes coerce participation and thereby compromise ethical research. This paper seeks to discuss some of the ethical issues arising from community engagement in a low resource setting.